Innovative integration of solar energy and pyrolysis technology in fish smoking for improved liquid smoke yield and quality - Risse Entikaria Rachmanita; Haning Hasbiyati; Refa Firgiyanto; Mohamad Anggis Safii Wijaya; Isrolana; Ellya Dwi Lestari; Bayu Rudiyanto (Mechanical Engineering for Society and Industry, 2026)
Traditional fish smoking still causes environmental pollution and health issues due to uncontrolled smoke emissions. Field data indicate that 54.0% of workers in fish smoking centers are exposed to heavy smoke, and 66.7% experience severe respiratory symptoms, underscoring the need for cleaner technologies. This study developed an integrated solar-powered fish smoking system combining pyrolysis and a naturally cooled spiral condenser to convert combustion smoke into liquid smoke as a natural preservative. The prototype was designed and tested using corn cob biomass as the pyrolysis feedstock. Evaluated parameters included solar panel efficiency, smoking chamber performance, and liquid smoke quality. Characterization covered specific gravity, pH, acetic acid, phenol content, and heavy metals (Pb, Cd). Results showed that pure corn cob liquid smoke had a specific gravity of 0.99965 g/cm³, pH 3.55, acetic acid 1.747%, and phenol 7.8859%, while smoke applied to fish yielded 1.008572 g/cm³, 3.70, 3.950%, and 12.4242%, respectively. Both Pb and Cd were not detected (< LOD), confirming safety from contamination. Although acetic acid and phenol contents correspond to SNI 8985:2021 grade 2, further purification is needed to meet food-grade standards. The system effectively produces functional, antimicrobial liquid smoke while reducing emissions, supporting sustainable fish smoking and the circular economy.